Can Transition Planning Become More Autism Friendly? - Papdakis, Bernadette (2009)
The current multi-strategy study addressed the paucity of research examining the effectiveness of ‘transition planning’ and particularly its suitability for young people with autism. This study employed a review of the literature and a multi-strategy of quantitative and qualitative research to investigate the issues associated with this intervention, and the ways in which the experience could be improved for young people with autism. Findings indicated deficits in the system as a whole, as relevant to all young people with SEN, in that there appear to be significant implementation gaps between transition planning policy and practice. In terms of autism and ways to make planning more ‘autism friendly’, findings identified multi-agency liaisons, staff training, alternative systems of communication and specialist services as areas in which improvements could be made to better support the transition from school to adulthood for these young people. Throughout this enquiry, the authors’ personal reflections suggest how consideration of these issues can deepen understanding, knowledge and professionalism in the workplace.